Valeriana officinalis dry plant extract for direct compression: Preparation and characterization - Gallo, Loreana Carolina (2012)
Valeriana officinalis L. (Valerianaceae) is one of the most widely used plants for the treatment of anxiety and insomnia. Usually dry plant extracts, including V. officinalis, are hygroscopic materials with poor physico-mechanical properties that can be directly compressed. A V. officinalis dry extract with moderate hygroscocity is suitable for direct compression, and was obtained by using a simple and economical technique. The V. officinalis fluid extract was oven-dried with colloidal silicon dioxide as a drying adjuvant. The addition of colloidal silicon dioxide resulted in a dry plant extract with good physico-mechanical properties for direct compression and lower hygroscopicity than the dry extract without the carrier. The dry plant extract glass transition temperature was considerably above room temperature (about 72 °C). The colloidal silicon dioxide also produced an antiplasticizing effect, improving the powder's physical stability. The pharmaceutical performance of the prepared V. officinalis dry extract was studied through the design of tablets. The manufactured tablets showed good compactability, friability, hardness, and disintegration time. Those containing a disintegrant (Avicel PH 101) exhibited the best pharmaceutical performance, having the lowest disintegration time of around 40 seconds.